A study on the material performance of the two brands of underwear with relation to price. - Kwan, Roselle Maida
This is a study on the material performance of two underwear products produced by two competing brands. The purpose of this study is to determine the performance of the materials used by the two products. Performance in this context would mean serviceability or fitness "for purpose". The raw materials to be tested for performance are the elastic material and fabric used. In order to obtain results for the study, laboratory tests had to be conducted on the products. Thirty samples of the two underwear products were tested in the laboratory for material performance in terms of fabric strength, elongation, dimensional change, and colorfastness, properties which all relate to material performance. Random sampling was used in gathering data for this research. Primary sources of data were laboratory test results. The brands were encoded as 300-98 and 301-98. Test results reveal that brand 300-98 is greater by 3.2 lbs./ in^2 in bursting strength, and higher by 3.15% in elongation performance than brand 301-98. Brand 300-98 is therefore the underwear having higher material performance.